Location Based Services (LBS) for Searching Tire Repair Location in Banjarbaru City Based on Android - Desy Ika Puspitasari; Mirza Yogy Kurniawan (Jurnal Fisika FLUX, 2019)
The tire repair location is one of the determining factors sought by motorized vehicle users if they are experiencing a tire leak in the middle of a trip. This makes vehicle users panic and think to immediately look for the nearest tire repair location. Banjarbaru City has 5 sub-districts and 12 villages, and is the center of the South Kalimantan Province administration. Given the large number of settlements, especially now that there are many housing complexes in Banjarbaru, this automatically makes the number of new roads opened by the local government. Actually this can be an opportunity for tire repair entrepreneurs to open tire repair locations in several places, because nowadays there are still very few workshops or tire repair locations in the new residential area.Location Based Service System, or better known as LBS, combines the process of a mobile service with the geographical position of its users. The important point is when the target position, where a target might be an LBS user or another entity that is incorporated in a service. This research leads to android based applications and services that provide information of tire repairlocation, to make it easier for motorbike riders to find tire repair locations based on available facilities.